Can A Multivariate Model for Survival Estimation in Skeletal Metastases (PATHFx) Be Externally Validated Using Japanese Patients?. Issue 9 (September 2017) - Ogura, Koichi; Gokita, Tabu; Shinoda, Yusuke; Kawano, Hirotaka; Takagi, Tatsuya; Ae, Keisuke; Kawai, Akira; Wedin, Rikard; Forsberg, Jonathan A.
Abstract: Background: Objective survival estimates are important when treating or studying outcomes in patients with skeletal metastases. One decision‐support tool, PATHFx (www.pathfx.org ) is designed to predict each patient's postsurgical survival trajectory at 1, 3, 6, and 12 months in patients undergoing stabilization for skeletal metastases. PATHFx has been externally validated in various western centers, but it is unknown whether it may be useful in Asian patient populations. Questions/purposes: We asked (1) whether the PATHFx models are as predictive in Japanese patients by estimating the area under the receiver operator characteristic curve (AUC); we considered an AUC greater than 0.7 as an adequate predictive value. We also (2) performed decision curve analysis at various times to determine whether and how PATHFx should be used clinically at those times. Patients and Methods: A Bayesian model is a statistical method to explore conditional, probabilistic relationships between variables to estimate the likelihood of an outcome using observed data. We applied the PATHFx Bayesian models to an independent dataset containing the records of patients who underwent skeletal stabilization for metastatic bone disease at one of five Japanese referral centers and had a followup longer than 12 months for survivors. Of 270 patients in the database, we excluded nine patients from analysis because their followup was less than 12 months, and finally we included 261 patients in the analysis. Data examined included age at the time of surgery, sex, indication for surgery (impending fracture or completed pathologic fracture), number of bone metastases (solitary or multiple), presence or absence of visceral or lymph node metastases, preoperative hemoglobin concentration, absolute lymphocyte count, and the primary oncologic diagnosis. We performed receiver operating characteristic curve analysis and estimated the AUC as a measure of discriminatory ability. Decision curve analysis was performed to determine if and how the models should be used in the clinical setting. Results: The AUCs for the 1‐, 3‐, 6‐, and 12‐month models were 0.77 (95% CI, 0.63‐0.86), 0.80 (95% CI, 0.72‐0.87), 0.83 (95% CI, 0.77‐0.89), and 0.80 (95% CI, 0.75‐0.86), respectively. Decision analysis indicated that the models conferred a positive net benefit (above the lines assuming none or all survive at each time) although the CIs of the AUC for 1 month were wide, suggesting that this dataset could not adequately predict 1‐month survival. Conclusions: Our findings show PATHFx is suitable for clinical use in Japan and may be used to guide surgical decision making or as a risk stratification method in support of clinical trials involving Japanese patients at 3, 6, and 12 months. More studies will be necessary to confirm the validity of the 1‐month survival predictions of this mode. Other patient populations will need to be studied to confirm its usefulness in other non‐Western and non‐Japanese populations. Level of Evidence: Level II, prognostic study.